Removal of colour from textile wastewater using oil palm ash - Yap, J.; Isa, M.H.; Kutty, S.R.M. (2008)
The present study explores the possibility of using a low cost adsorbent i.e. oil palm ash, for the treatment of coloured effluent from a textile industry. The adsorbent was obtained locally from a palm oil mill and was used for the study with no pretreatment. The effects of different system variables, viz., pH, initial colour (wastewater) concentration and agitation time were studied in the batch tests. Different strengths of wastewater (10%, 20%, 40%, 60%, 80%, 100%) were obtained by suitably diluting of the original effluent sample. Acidic pH was found to favour colour removal. The optimum pH and agitation time for the removal of colour from the textile wastewater were 1 and 4 hr, respectively. Both Langmuir and Freundlich isotherms could be used to describe adsorption of colour from the effluent, with the latter yielding a slightly better fit. Kinetic studies showed that the experimental data was better described by the pseudo-second order kinetic model then the pseudo-first order kinetic model. Oil palm ash has the potential to be used as a low cost adsorbent for colour removal from aqueous solution.